Integrated assessment modelling of environmental impacts of land use policy in West-Africa: A conceptual model - (:unkn) unknown (My University, 2015)
This communication discusses considerations for the establishment of a spatialized computer model formalizing a prospective of the environmental impacts of public policies regarding land uses. This objective, once applied in West Africa, needs to face several challenges specific to the sub-region: on the one hand, the difficulty of creating a set of data strong enough for enabling the modelling process and on the other hand, the integration of the high variability of its environment, both biophysical (rainfall first) and socially (land tenures first).
Keywords: African Research